Determinants of Community Participation in the COVID-19 Vaccination Program - Asmin, Elpira; Leunupun, Delsony Gerson; Eka Astuty (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus, which is transmitted mainly through saliva or secretions from the nose when an infected person coughs or sneezes. One way to prevent the broader spread of the COVID-19 pandemic is by vaccination. The study aimed to determine factors related to community participation in the COVID-19 vaccination program in Batu Merah State, Ambon City, in 2021. This study was an analytical study using primary data with a cross-sectional approach. The sample in this study consisted of residents of Batu Merah State, Ambon City, aged 18 years, totaling 204 people who were taken using the cluster random sampling technique. 59 respondents (28.9%) had received the first dose of vaccination, and as many as 42 respondents (20.6%) had received the first and second doses of vaccination. Meanwhile, as many as 103 respondents (50.5%) have not been vaccinated. The role of the environment is mainly found in the supportive category, which is 136 respondents (66.7%), the most motivation is in the medium category, which is 125 respondents (61.3%), the most economical level is in the lower middle category as many as 117 respondents ( 57.4%), the highest confidence was in the medium category, which was 110 respondents (53.9%), and the most convenience was in the relatively easy category, which was 163 respondents (79.9%). There is a relationship between the role of the environment, motivation, economic level, confidence, and convenience with community participation in the COVID-19 vaccination program in Batu Merah State, Ambon City, in 2021. Suggestion to Batu Merah people who have not been vaccinated to come to the nearest health center.